Aortic Pulse Wave Analysis is not a surrogate for central arterial Pulse Wave Velocity - Gurovich, Alvaro N; Beck, Darren T; Braith, Randy W (Experimental biology and medicine (Maywood, N.J.), 2009)
Arterial Stiffness (AS) is a primary cardiovascular risk factor. AS increases myocardial oxygen demand and LV work and decreases coronary perfusion. Pulse Wave Velocity (PWV) is considered the gold standard for assessing AS. However, PWV testing is time consuming and impractical in the clinical setting. The purpose of this study was to determine if Pulse Wave Analysis (PWA) parameters obtained with applanation tonometry can be used to predict PWV. Radial artery PWA testing and aortic PWV measurements were performed on 77 apparently healthy subjects. A correlation matrix between all the studied variables and a stepwise multiple regression were performed. The best regression equation was obtained with central PWV as the dependent variable and Age, Height, Weight, Brachial Systolic and Diastolic Blood pressures, normalized and non-normalized Augmentation Index, Cardiac Cycle time, Ejection Duration, reflected wave round trip travel time, and time to peak pressure as independent variables. Finally, a Bland-Altman test was performed to determine the agreement between measured and predicted PWV. No significant correlations between PWV and PWA parameters were found. The resulting stepwise regression equation was PWV = 1.76 + 0.044*Age + 0.023*SBP (R = 0.544, Adj-R(2) = 0.28, P < 0.001). No agreement between measured and predicted PWV was observed using the Bland-Altman test. Although the regression equation is significant, the adjusted coefficient of determination shows that the model could explain just 28% of PWV variability. These findings suggest that PWA should not be used as a surrogate measure for assessing aortic PWV and stiffness.